AMAL YANG PAHALANYA TIDAK AKAN TERPUTUS BAGI MAYIT - Fitria N. Laiya (CV. Adiba Aisha Amira, 2024)
The existence of life after death is one of the things that Muslims believe in. This is something that is not only believed to be true, it is even practiced in human life throughout the world. After a person dies, all his practices are interrupted, except for 3 things. These three things include: almsgiving, useful knowledge, and prayers for pious children. Almsgiving includes all good deeds given to other people that have benefits for many people. This goodness can be material and non-material. Alms in the form of materials, for example building hospitals, schools, mosques and so on. Non-material alms can be in the form of ideas, energy and time given for the benefit of the Muslim Ummah. Useful knowledge, meaning someone who teaches other people, with this knowledge other people can do good, can get closer to God and can be put into practice in everyday life. Next, pray for a pious child. A pious child will be an obstacle for his parents from going to hell. The prayers that devout children continue to offer to their parents will slowly erase their parents' sins. Therefore, every parent competes to educate their children to become pious children. . To obtain in-depth research, this hadith was researched using the tahlili method. In the order of tracing hadith through takhrij al-hadith, sanad study and matan study. After conducting research on the sanad and matan hadith in the al-Nasa'i route, it was discovered that the sanad was of authentic quality, as was the matan. Therefore, it can be concluded that this hadith is of authentic quality. After conducting research on the practices that will not be interrupted for the dead, it was found that there are five hadith editors which are narrated with meaning. These five narrations are found in the books of Sahih Muslim, Sunan Abu Dawud, Sunan at-Tirmidhi, Sunan an-Nasai and Musnad Ahmad bin Hanbal. Apart from that, it was also found that each narration does not contradict the verses of the Koran and other authentic hadiths. This is the basis for determining the quality of this hadith.